An epidemiological investigation of high-risk infants for Respiratory Syncytial Virus infections: a retrospective cohort study - Michela Servadio; Marco Finocchietti; Chiara Vassallo; Riccardo Cipelli; Franca Heiman; Giulia Di Lucchio; Bianca Oresta; Antonio Addis; Valeria Belleudi (BMC, 2024)
Abstract Background Respiratory Syncytial Virus (RSV) infections may lead to severe consequences in infants born preterm with breathing problems (such as bronchopulmonary dysplasia (BPD) and respiratory distress syndrome (RDS)) or congenital heart diseases (CHD). Since studies investigating the influence of different gestational age (WGA) and concomitant specific comorbidities on the burden of RSV infections are scarce, the present study aimed to better characterize these high-risk populations in the Italian context. Methods This retrospective, longitudinal and record-linkage cohort study involved infants born between 2017 and 2019 in Lazio Region (Italy) and is based on data extracted from administrative databases. Each infant was exclusively included in one of the following cohorts: (1) BPD-RDS (WGA ≤35 with or without CHD) or (2) CHD (without BPD and/or RDS) or (3) Preterm (WGA ≤35 without BPD (and/or RDS) or CHD). Each cohort was followed for 12 months from birth. Information related to sociodemographic at birth, and RSV and Undetermined Respiratory Agents (URA) hospitalizations and drug consumption at follow-up were retrieved and described. Results A total of 8,196 infants were selected and classified as 1,084 BPD-RDS, 3,286 CHD and 3,826 Preterm. More than 30% of the BPD-RDS cohort was composed by early preterm infants (WGA ≤ 29) in contrast to the Preterm cohort predominantly constitute by moderate preterm infants (98.2%), while CHD infants were primarily born at term (83.9%). At follow-up, despite the cohorts showed similar proportions of RSV hospitalizations, in BPD-RDS cohort hospitalizations were more frequently severe compared to those occurred in the Preterm cohort (p<0.01), in the BPD-RDS cohort was also found the highest proportion of URA hospitalizations (p<0.0001). In addition, BPD-RDS infants, compared to those of the remaining cohorts, received more frequently prophylaxis with palivizumab (p<0.0001) and were more frequently treated with adrenergics inhalants, and glucocorticoids for systemic use. Conclusions The assessment of the study clinical outcomes highlighted that, the demographic and clinical characteristics at birth of the study cohorts influence their level of vulnerability to RSV and URA infections. As such, continuous monitoring of these populations is necessary in order to ensure a timely organization of health care system able to respond to their needs in the future.